Радиационные потери элементов связи зеркального дискового диэлектрического резонатора. Часть 2. Связь с рассогласованными волноводами - Гламаздин, В.В.; Натаров, М.П.; Скресанов, В.Н.; Шубный, А.И. (Радіофізика та електроніка, 2015)
Исследованы радиационные потери элементов связи (ЭС) зеркального дискового диэлектрического резонатора (ЗДДР) с модами шепчущей галереи для случая связи с рассогласованными волноводами. Результаты исследования представляют особый интерес для разработчиков автогенераторов с использованием ЗДДР, когда полупроводниковые приборы с цепями согласования импедансов расположены в волноводах, образуя комплексную нагрузку. Досліджено радіаційні втрати елементів зв’язку (ЕЗ) дзеркального дискового діелектричного резонатора (ДДДР) з модами шепочучої галереї з неузгодженими хвилеводами. Результати дослідження мають особливий інтерес для розробників автогенераторів з використанням ДДДР, коли напівпровідникові прилади з колами узгодження імпедансу розташовані у хвилеводах, утворюючи комплексне навантаження. The coupling radiation loss of the whispering gallery mode mirror dielectric disk resonator (MDDR) with mismatched waveguides was researched. The findings are of particular interest to the developers of MDDR solid-state oscillators where semi-conductor devices and impedance matching circuits are located in the waveguide, forming a complex load in the waveguide. The dependences of MDDR resonance frequency and Q-factor on the amplitude and phase of the wave reflected from inhomogeneities in the waveguide back to the resonator are measured. Two types of couplers (a hole in the diaphragm on the mirror and an open end of the narrower waveguide on the mirror) are studied. For the open end type coupler it has been shown that MDDR resonant frequency and Q-factor can be calculated using the proposed lumped elements scheme of MDDR coupler and measuring procedure described in the first part of this paper. Coupling radiation loss and Joule loss in the load which are brought in MDDR by the complex load in the waveguide are calculated.